Tall oil e seus subprodutos: alternativas como preservantes para madeira - Bossardi, Kelly [UNESP] (2014)
Traditional methods of wood protection employ chemicals that are considered toxic and can harm human health and the environment. Increasing concern about environmental issues, with the health of process operators to preservative treatment of timber and consumers, and with the reuse this timber treated after use, has generated the need for development of less aggressive treatments condoms to health and the environment. The aim of this study was to test the capability of three conditions of samples from Tall Oil in two species for reforestation wood: Pinus elliottii and Eucalyptus grandis. The alternatives were tested tall oil Crude tall oil (CTO), which is a by-product in the processing of coniferous softwood pulp for the production of kraft paper and two by-products from the refining of CTO, the ligth Oil (LO) and the Oil ejector (OE). These alternatives were tested isopropyl and 25% solution in combination with boric acid in a 2% aqueous solution. In samples with the systems of protection; tests hydrophobicity and exposure to white rot fungus (Fr.) Pilát Trametes versicolor (L.) were performed. The hydrophobicity assay was performed by measuring the contact angle on a goniometer. The test was conducted rotting providing the specimens treated soil inoculated with the fungus. The most satisfactory results were obtained with treatments with Ejector Oil, which showed hydrophobicity of 55%, both for pine as for eucalyptus, and mass loss of 39.07% for eucalyptus and 39.18% for pine after test exposure apodrecedor fungus. And for systems with boric acid mass loss was lower, being for AB + OE mass loss was 19.05% for eucalyptus and 19.96% for pine; and the OE / AB system and 13.43% for eucalyptus and 14.16% for pine